Characteristics of Sukuk and Their Influence on Financial Stability of Malaysian Firms - Chen, Xiaoting (Universiti Malaysia Sarawak (UNIMAS), 2019)
Financial stability and Sukuk expanded into the financial market quickly after the global financial turmoil which had happened from 2007 to 2008. The economy globalization has made financial stability difficult to achieve. While Malaysia's Sukuk market is arguably the most prominent in Islamic finance globally, the inherent nature of Sukuk gives it better security on the premise of guaranteed firms’ financial stability and returns to investors. This study aims to evaluate the degree of Malaysian firms’ financial stability which could be influenced by the characteristics of Sukuk and also firms’ characteristics. Sixty-one out of 164 companies that were listed on Bursar Malaysia which issued Sukuk have been selected for this study, and the issuance took place from 1997 to 2017. Subsequently, the firms’ financial stability was treated as default probability and determined by using Nai ̈ve Distance to Default (DD) which was developed by Bharath and Shumway. Descriptive analysis and Ordinary Least Squares (OLS) were employed in this study, and the results of the analysis confirmed that Sukuk could promote the firms’ financial stability. Among the important variables related to the characteristics of Sukuk that were found to influence financial stability were the intensity of Sukuk and the proportion of Sukuk. They were found to be positively and significantly influenced the firms’ financial stability. The control variables which include the firm size, valuation, solvency, and profitability have also affected the firms’ financial stability significantly. The findings provide evidences that Malaysia should play more active role in promoting the development of Sukuk market, and at the same time should be aware that financial stability is a systematic element which involved many complex factors. Thus, it is essential for companies and countries to comprehensively grasp the financial stability from macro and micro perspectives.